Human Sexual Development is Subject to Critical Period Learning: Implications for Sexual Addiction, Sexual Therapy, and for Child Rearing. - Griffee, Karen; O'Keefe, Stephen L.; Beard, Keith W.; Young, Debra H.; Kommor, Martin J.; Linz, Thomas D.; Swindell, Sam; Stroebel, Sandra S. (Sexual Addiction & Compulsivity)
A novel orientation-neutral Hypersexuality and Risky Sexual Behaviors Scale provided evidence consistent with the idea that both sexual addiction and a low interest in sex as an adult have their origins during childhood and adolescence. Adult interest in sex and the likelihood of engaging in risky sexual behaviors tended to be increased if participant's first experiences with masturbation and partner sex had occurred early in life. Conversely, adult interest in sex tended to be lowest when neither masturbation nor sex with a partner had occurred prior to 18 years of age. Both findings were consistent with critical period learning.